Circulating Tumor DNA: Unravelling the Treatment Response Uncertainty in Lymphoma: Systematic Review and Meta-Analysis - Bulain, Stanley; Setiawan, Aurielle Annalicia; Nestovani, Anggella Christoferisa Ditya; Pamarta, Trisna Belani; Baliulina, Shintya Octaviana; Arifah, Nina Nur (Universitas Brawijaya, 2026)
Background: Uncertainty in lymphomas treatment response could negatively affect the disease course. Circulating tumor DNA (ctDNA), minimally invasive biomarker, can be useful to monitor treatment response, recurrence, yet minimally invasive. Aim: To evaluate the effectiveness of ctDNA for predicting early relapse (indicated by progression-free survival (PFS) and overall survival (OS)), and for predicting non-complete response (non-CR) in lymphomas. Methods: Comprehensive searches in PubMed, ScienceDirect, Wiley, Springer and Cochrane were conducted. Critical appraisal was conducted using the ROBINS-E tool for cohort and ROB 2.0 randomized controlled trials. hazard ratios (HRs) of pretreatment CtDNA for PFS and OS. The secondary outcome was the risk ratio (RR) of non-CR in detectable posttreatment CtDNA and its diagnostic accuracy analysis. RevMan 5.4 and STATA 17 was used for quantitative analysis. Results: 14 studies (1,144 patients) were included. Higher pretreatment ctDNA significantly increase the risk of worse PFS (HR 2.20, 95% CI 1.41-3.43) and worse OS (2.20, .14-4.26), also with optimal cut-off at 2.5 log10hGE/mL for PFS (2.46, 1.70-3.54) and OS (2.36, 1.30-4.29). The value was also significant in DLBCL, both for PFS (2.46, 1.71-3.55) and OS (2.70, 1.58-4.60), P<0.05 . Detectable posttreatment CtDNA also correlated with non-CR (RR 5.56 95% CI 2.82-10.95), with pooled sensitivities 0.91 (0.71-0.98), specificities 0.76 (0.51-0.90), positive-likelihood ratios 3.74 (1.71-8.19), negative-likelihood ratios 0.12 (0.04-0.39), and area under curve (AUC) 0.91 (0.88 - 0.93). Conclusion: Higher pretreatment CtDNA strongly correlated with the disease progression and survival, specifically at log10hGE/mL. Detectable posttreatment CtDNA were significantly correlated with non-CR.